The determinants that affect the profitability of International Islamic Banking in Malaysia / Nur Afizah Amran - Amran, Nur Afizah (2011)
The paper analyzes how internal and external variables affect the profitability of International Islamic banks in Malaysia. The profitability calculated by using Rate of Return on Asset (ROA). Utilizing bank level data, the study examines the profitability indicators of International Islamic bank in Malaysia for every quarter during year 2007until 2009. This research used Al-Rajhi Bank as a sample since Al-Rajhi Bank is the most profitable among other Foreign Islamic Bank during a year 2009 in Malaysia. A variety of internal and external indicators were used to predict profitability and efficiency. The researcher used Inflation and Gross Domestic Product (GDP) in Malaysia as the external variables meanwhile internal variables consist of Overhead Cost and Risk-Weighted Capital Ratio (RWCR). The result shows that only GDP have strong positive relationship with International Islamic Bank profit in Malaysia. Surprisingly, the result indicates that no significance relationship between International Islamic Bank profit with inflation rate, overhead cost and RWCR.